(untitled) (Fiep Bulletin - online, 2016)
Chronic obstructive pulmonary disease (COPD) is a disease characterized by expiratory airflow obstruction, and then installed it is treatable, but irreversible. Participation in pulmonary rehabilitation program provides positive results for patients with COPD, decrease as periods of hospitalization because it improves the efficacy of respiratory and appendicular muscle work. This study is characterized with uncontrolled clinical trial, which was conducted at São Lucas/FAG Hospital of Cascavel PR. Participated in this research, 6 COPD patients, who haveevaluation of respiratory muscle strength and hemodynamic changes pre/post pulmonary rehabilitationprogram. Met clinical improvements, and values ??of respiratory muscle strength, however not considered statistically significant changes. At the end conclude there wasn’t statistical improvement, but the improvement of tabular datapost rehabilitation was visible in the population studied.